Considerations and challenges in longitudinal studies of lexical features in L2 writing - Minkyung Kim (Vocabulary Learning and Instruction, 2021)
Exploring the longitudinal development of second language (L2) lexical use has been one of the important topics in L2 vocabulary research. One approach to examining longitudinal changes in L2 lexical use is to capture changes in lexical features as found in learner production, such as L2 writing, over time. To further facilitate this approach, the purpose of this article is to discuss considerations and challenges for conducting longitudinal studies on lexical features in L2 writing. The article first provides a summary of relevant previous studies, followed by the promise of longitudinal studies on lexical features in L2 writing. It then presents considerations and challenges in longitudinal studies of lexical features in L2 writing in terms of the data collection and analysis and the choice of lexical measures. More research on the longitudinal changes in lexical features in L2 learner production seems warranted. Ultimately, more longitudinal research in lexical features in L2 learner production will help us have a deeper understanding of L2 lexical development and design better vocabulary intervention in L2 classrooms.